User-Library Interface: A Key Approach to LIS Marketing - Gupta, Dinesh K.R. (Journal of Information and Knowledge, 1996)
Ultimate goal of all library and information service activities is to provide access to maximum user satisfaction or delight. The paper describes the importance of relationship between user and L&I centre, which provides L&I managers to understand users in the best way and involves strategies to improve access, quality and offerings and overall, committed to user satisfaction or delight. A model for user-relationship in L&I centres is also outlined.